2022
DOI: 10.4047/jap.2022.14.3.150
|View full text |Cite
|
Sign up to set email alerts
|

Trueness of 3D printed partial denture frameworks: build orientations and support structure density parameters

Abstract: PURPOSE The purpose of the study was to assess the influence of build orientations and density of support structures on the trueness of the 3D printed removable partial denture (RPD) frameworks. MATERIALS AND METHODS A maxillary Kennedy class III and mandibular class I casts were 3D scanned and used to design and produce two 3D virtual models of RPD frameworks. Using digital light processing (DLP) 3D printing, 47 RPD frameworks were fabricated at 3 different build orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Based on the results of our study, the 120-degree angle demonstrated less surface roughness than the 135-degree angle, which confirms the influence of the build orientation. 24,25 However, the difference between them was not statistically significant to recommend one build orientation over the other. These findings could be attributed to the simplicity of the specimen shape configuration used in this study, and may reflect different results if an actual denture print was to be considered.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Based on the results of our study, the 120-degree angle demonstrated less surface roughness than the 135-degree angle, which confirms the influence of the build orientation. 24,25 However, the difference between them was not statistically significant to recommend one build orientation over the other. These findings could be attributed to the simplicity of the specimen shape configuration used in this study, and may reflect different results if an actual denture print was to be considered.…”
Section: Discussionmentioning
confidence: 88%
“…The specimens were subjected to post-processing curing for 20 minutes in an Asiga Flash post-curing chamber (ASIGA, Sydney, Australia) following which all the supports were removed. 25 The printed specimens were measured (65 Â 10 Â 3.3 mm) first by the same operator to ensure standardization and then finished using silicon carbide (mega-Schmirgelleinen; megadental, Büdingen, Germany) followed by acrylic polishing burs (Shofu Dental Corporation, San Marcos, California, United States), pumice (Kemdent Works, Wiltshire, United Kingdom) and high shine polishing compound (Keystone Industries, New Jersey, United States).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework can be created on a three-dimensional (3D) model created from 3D scans of the working cast by utilizing this technology. 5 The duties of a dental surveyor (identifying insertion and removal directions, outlining the framework design, blocking out the working cast, applying for relief, and finalizing the wax-up of the framework) can now be accomplished digitally. This digitization speeds up the fabrication procedures, lowers material costs, and minimizes time by reducing the necessity for several impressions and refractory casts that traditional casting requires.…”
mentioning
confidence: 99%
“…Using computer‐aided design and computer‐aided manufacturing (CAD‐CAM) innovations in metal frameworks fabrication for removable partial dentures is increasing. The framework can be created on a three‐dimensional (3D) model created from 3D scans of the working cast by utilizing this technology 5 . The duties of a dental surveyor (identifying insertion and removal directions, outlining the framework design, blocking out the working cast, applying for relief, and finalizing the wax‐up of the framework) can now be accomplished digitally.…”
mentioning
confidence: 99%